Contradictions of Class and Consumption When the Commodity Is Labour - Barber, Pauline Gardiner (Anthropologica, 2022)
This paper poses a critique of globalization discourse through an examination of Philippine migration ethnography. With the dramatic increase in scale in the mid-1980s, Philippine gendered labour migration has been subjected to scrutiny by academics and other protagonists raising the possibility of a critical Philippine transnational politics. However, the relatively new ethnographic literature explores the constrained labour process of domestic service work and cultural practices which condition migrants for exploitation. Class issues remain largely unexplored in this literature for theoretical and methodological reasons. Here, multisited research enables the mapping of contradictions of class and consumption associated with the normalization of migration in Philippine society and politics. The complexities of production and consumption surround the migration industry are also discussed.